WB-Cleaner Si Penghapus Permanent Marker - Suhendi, Suhendi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The one of Effective instructional media in order to support the success of the learning process isthe board or (white boards). But in use, whiteboard can hinder the effectiveness of the learning process when the slates used are dirty due to the rest of the previous posts. This is because the eraser which used is not really able to delete the post until the whiteboard clean as new. Generally, the eraser made of fabric designed with wood or plastic and does not remove the whiteboard until completely clean, so the whiteboard that has a very dirty usually would replaced with a new one, but if seen in terms of the physical is still good , but it is no longer effective if used continue, so inevitably the whiteboard must be replaced. But if there is a cleaner that can clean the whole lifetime of the slates may be longer and better teaching effectiveness and cost savings in the field of education expenses to buy a new whiteboard. But until now there is no specific product that is designed to clean up the remnants of markers on a whiteboard markers either regular or permanent markers. Therefore, for a more durable whiteboard, we provide a solution to make The Whiteboard cleaner liquid-based natural that we refer to as